A diagnostic challenge in an unresponsive refugee child improving with neurosurgery—a case report. Issue 5 (24th May 2021) - Makris, George; Papageorgiou, Nefeli; Panagopoulos, Dimitrios; Brubakk, Katrin Glatz
ABSTRACT: An unresponsive paediatric patient may present a diagnostic challenge for health professionals, as rapid identification of the cause is needed to provide proper interventions. The following report details a challenging diagnosis of unresponsiveness in a refugee child. In the migratory context, observed unresponsiveness states are frequently attributed to psychologic factors, and overlapping psychiatric classifications (resignation syndrome, functional coma and catatonia) are common. Our patient fell into an unresponsive state for 6 months after witnessing a traumatic event. Diagnostic workup for multiple medical comorbidities led to surgical intervention for tethered cord syndrome. Shortly after that, the patient's responsiveness improved, putting to question her condition's underlying cause. This case highlights the need for a biopsychosocial approach in such cases, reflected in thorough clinical examination and diagnostic investigations. A multidisciplinary perspective and expertise proved crucial and may help in the rehabilitation of children in similar situations.